Bibliometric Analysis of Islamic Money Market Research: Mapping Trends, Networks And Opportunities - Andriyanto, Gian Anggraeni; Mukti, Titania (FEB Universitas Sultan Ageng Tirtayasa, 2024)
Islamic money market is part of short-term financial instruments. The development of Islamic money market is quite rapid in recent times. This study aims to map and analyze research trends on Islamic money market using bibliometric approach. Data sources were collected from the Scopus database using the search keyword